Principles Analysis Of Grice's Cooperation In Events Speech In Traditional Markets: A Pragmatic Study - Riska Yulfiana; Dian Sari Unga Waru; Rudy Yusuf; Ince Nasrullah; yusmah Yusmah; Firman Saleh (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Speakers and speech partners in a speech event cannot be separated from the rules governing the act of using language so that speech can run well. One of the language principles in pragmatic studies is the cooperative principle or Grice's cooperative maxims which divide the principles in question namely, 1) maxim of quantity, 2) maxim of quality, 3) maxim of relevance ( maxim of relevance), and 4) maxim of manner. This research was conducted to find out the application of Grice's cooperation maxims in speech events in the market. The population of this study are all traders and buyers who are transacting within the market scope. Whereas, Sampling was determined using random sampling technique or random sampling by taking as many as 10 to 15 conversational samples in trader and buyer transactions. Data collection is carried out by tapping or recording techniques. Data analysis was carried out in three stages, namely, data reduction, data modeling, and drawing/verifying conclusions. It is obtained that three out of the four Grice cooperation maxims are fulfilled. This conclusion is drawn from the results of processing or analysis of data obtained during the research. The three maxims fulfilled include; 1) maxim of quantity, 2) maxim of quality, and 3) maxim of manner. Meanwhile, the maxim that is violated is the maxim of relevance. One of the reasons why the maxim of relevance is violated by traders is to divert attention. This aims to offer or introduce other merchandise when the goods needed by the buyer are not available or out of stock.